Kelimpahan Mikroplastik Pada Sedimen Sungai Air Hitam, Pekanbaru, Riau - Rilian Gerry Sitompul; Lita Darmayanti; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Microplastics are plastic sinks measuring <5 mm. Process analysis along on the sediment carried through several stages, namely drying, filtering, sorting visually, the separation of the density (flotation), analysis using a microscope. The most dominate type of microplastic is fragment with a percentage of 49.58%, then film about 27,73%, and fiber about 22,69%. Microplastics in the sediments of the Air Hitam River are thought to come from household waste, disposable plastics waste (plastic bags, plastic bottles, food and beverage packaging), and waste from the tofu industry.Keywords : Microplastics, Abundance, Sediment, Air Hitam River